Advantages and limitations of commonly used methods to assay the molecular permeability of gap junctional intercellular communication. (July 2008) - Abbaci, Muriel; Barberi-Heyob, Muriel; Blondel, Walter; Guillemin, François; Didelon, Jacques
The role of gap junctional intercellular communication (GJIC) in regulation of normal growth and differentiation is becoming increasingly recognized as a major cellular function. GJIC consists of intercellular exchange of low molecular weight molecules, and is the only means for direct contact between cytoplasms of adjacent animal cells. Disturbances of GJIC have been associated with many pathological conditions, such as carcinogenesis or hereditary illness. Reliable and accurate methods for the determination of GJIC are therefore important in cell biology studies. There are several methods used successfully in numerous laboratories to measure GJIC both in vitro and in vivo. This review comments on techniques currently used to study cell-to-cell communication, either by measuring dye transfer, as in methods like microinjection, scrape loading, gap-fluorescence recovery after photobleaching (gap-FRAP), the preloading assay, and local activation of a molecular fluorescent probe (LAMP), or by measuring electrical conductance and metabolic cooperation. As we will discuss in this review, these techniques are not equivalent but instead provide complementary information. We will focus on their main advantages and limitations. Although biological applications guide the choice of techniques we describe, we also review points that must be taken into consideration before using a methodology, such as the number of cells to analyze.